Validity and reliability of 6-minute pegboard and ring test in patients with asthma. (13th June 2022) - Calik-Kutukcu, Ebru; Tekerlek, Haluk; Bozdemir-Ozel, Cemile; Karaduz, Beyza Nur; Cakmak, Aslihan; Inal-Ince, Deniz; Saglam, Melda; Vardar-Yagli, Naciye; Sonbahar-Ulu, Hazal; Firat, Merve; Arikan, Hulya; Kaya, Saltuk Bugra; et al.
Abstract: Objective: The 6-minute pegboard and ring test (6PBRT) is a test of upper-extremity functional capacity designed for and validated in chronic obstructive pulmonary disease. The aim of this study was to evaluate the validity and reliability of the 6PBRT in asthma patients. Methods: Thirty-four adults (30 women, 4 men) with well-controlled asthma were included. Unsupported upper-extremity exercise capacity was assessed using 6PBRT, maximal arm exercise capacity using an arm ergometer, handgrip strength using a hand dynamometer, activities of daily living with the London Chest Activities of Daily Living Scale (LCADL), Milliken ADL scale (MAS) and health-related quality of life using the Asthma Quality of Life Questionnaire (AQLQ) and Health Assessment Questionnaire Disability Index (HAQ-DI). Results: The 6PBRT showed moderate to excellent test–retest reliability with an intraclass correlation coefficient (ICC) value of 0.872 [95% confidence interval (CI) 0.702–0.941]. The 6PBRT was reproducible according to Bland–Altman analysis, with upper and lower limits of agreement of 53.51 and −25.08 rings moved, respectively. The 6PBRT score was significantly correlated with maximum workload ( r  = 0.514, p  = 0.002) achieved in the arm ergometer test, change in dyspnea during 6PBRT (r = −0.402, p  = 0.020), LCADL-self-care (r = −0.364, p  = 0.037), MAS total ( r  = 0.483, p  = 0.005), AQLQ-symptom domain ( r  = 0.420, p  = 0.026) and HAQ-DI total scores (r = −0.390, p  = 0.025). Conclusions: The 6PBRT can be used as a valid and reliable test to evaluate functional arm exercise capacity in patients with well-controlled asthma.